The Role of Non-Formal Education in School - დიდმანიძე მარინა; Didmanidze, Marina; Kuchava, Manana; Didmanidze, Didar (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
The role of non-formal education is great in school life, it provides not only academic knowledge, but also such skills (for example, communication, teamwork, creative thinking skills, etc.), which contributes to the successful integration of a person into society and his realization. Non-formal education contributes to improving outcomes in formal educational institutions (kindergarten, school, vocational school). It is a continuation of formal education that helps develop literacy, digital skills, life skills, and socio-cultural skills in students. By mastering these skills, the student prepares for independent living and becomes self-confident.